已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式 答案是c=4a^3*b^2 已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式答案是c=4a^3*b^2

来源:学生365bet投注专线_365bet官网无法打开_365bet取款帮助网 编辑:365bet投注专线_365bet官网无法打开_365bet取款帮 时间:2019/09/24 18:13:14
已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式答案是c=4a^3*b^2已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27

已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式 答案是c=4a^3*b^2 已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式答案是c=4a^3*b^2
已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式 答案是c=4a^3*b^2
已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式
答案是c=4a^3*b^2

已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式 答案是c=4a^3*b^2 已知a=3^(-m),b^(-1)=2^(1-n),c=4^n*27^(-m)试写出用a,b表示c的代数式答案是c=4a^3*b^2
b=2[-(1-n)]=2^(n-1)
c=(2^2)^n*(3^3)^(-m)
=2^2n*3^(-3m)
=2^(2n-2+2)*[3^(-m)]^3
=2^(2n-2)*2^2*a^3
=b^2*4*a^3
所以c=4a^3*b^2